Veterinarian burnout demographics and organizational impacts: a narrative review - Steffey, Michele A.; Griffon, Dominique J.; Risselada, Marije; Scharf, Valery F.; Buote, Nicole J.; Zamprogno, Helia; Winter, Alexandra L. (Frontiers in Veterinary Science, 2023)
Burnout is a work-related syndrome of physical and emotional exhaustion secondary to prolonged, unresolvable occupational stress. Individuals of different demographic cohorts may have disparate experiences of workplace stressors and burnout impacts. Healthcare organizations are adversely affected by burnt out workers through decreased productivity, low morale, suboptimal teamwork, and potential impacts on the quality of patient care. In this second of two companion reviews, the demographics of veterinary burnout and the impacts of burnout on affected individuals and work environments are summarized, before discussing mitigation concepts and their extrapolation for targeted strategies within the veterinary workplace and profession.